Accessing the Role of Party Politics in the Nigerian Elections - Adeyemi, Oluwatobiloba Deborah; Omolaja, Akolade Oluwaseunfunmi; Akindoyin, Dare Isaac (Kashere Journal of Politics and International Relations, 2025)
The Political parties are one of the most important aspects of electioneering. They serve as a platform where qualified citizenship representation can be processed and the aspiration of governmental positions can be achieved. Political parties under a liberal democratic system are expected to deepen democracy by ensuring credible, free, and fair primaries in selecting their various candidates for elective positions that would advance public welfare in line with party manifestos. However, politics within different political parties are intriguing. Politics within and among the various political parties in Nigeria can determine the mood of the electioneering period which can affect the election’s winner, leading to either good or bad governance. Adopting a qualitative research approach and the group theory as a theoretical framework the study finds that unavailability and lack of adherence to procedure, nepotism, godfatherism, ethnicity, disrespect for the rule of law, oppression, manipulation, abuse of the electoral system can throw some doubt as to whether political parties can promote credible, free and fair electoral process in Nigeria. The study concludes that the mechanism for a candidate’s emergence in Nigeria is to a great extent exclusive of the input of the masses. The study recommends that the Nigerian political system needs to be demonetized, political education needs to be improved through functional basic education, and the economy needs to be strengthened so that individuals are less inclined to enter politics out of laziness or the belief that it is a quick way to get rich.